2021
DOI: 10.2147/copd.s291920
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Success of Tiotropium/Olodaterol, Measured Using the Clinical COPD Questionnaire (CCQ), in Routine Clinical Practice: A Multinational Non-Interventional Study

Abstract: Background The Clinical COPD Questionnaire (CCQ) is a simple patient-reported tool to measure clinical control of chronic obstructive pulmonary disease (COPD). Objective This open-label, single-arm, non-interventional study (NCT03663569) investigated changes in CCQ score during treatment with tiotropium/olodaterol in clinical practice. Methods Data were included from consenting COPD patients, enrolled in Bulgaria, Czech Republic, Hungary, Isr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…Indeed, our study extends the previously reported findings by demonstrating that tiotropium/olodaterol Respimat has a beneficial effect not only in patients’ physical functioning (a potential surrogate for health status) but also in the overall health status of patients with COPD. To our knowledge, this study, together with a recent multinational study conducted by Valipour and colleagues [ 22 ] are the first observational studies assessing the effectiveness of tiotropium/olodaterol Respimat in improving the overall health status of COPD, both demonstrating consistent results in terms of clinically meaningful improvements on health status over a similar treatment period [ 22 ].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Indeed, our study extends the previously reported findings by demonstrating that tiotropium/olodaterol Respimat has a beneficial effect not only in patients’ physical functioning (a potential surrogate for health status) but also in the overall health status of patients with COPD. To our knowledge, this study, together with a recent multinational study conducted by Valipour and colleagues [ 22 ] are the first observational studies assessing the effectiveness of tiotropium/olodaterol Respimat in improving the overall health status of COPD, both demonstrating consistent results in terms of clinically meaningful improvements on health status over a similar treatment period [ 22 ].…”
Section: Discussionmentioning
confidence: 80%
“…The severity of dyspnea was measured via the modified Medical Research Council Dyspnea scale (mMRC). The mMRC is an ordinal four-point scale (grades 0–4) based on degrees of various physical activities that precipitate dyspnea, with grade 4 representing the most severe category [ 22 ]. mMRC together with exacerbation history, and GOLD spirometric classification of airflow limitation (if available) were also used to automatically calculate the GOLD patient group (B, C or D) within the electronic Case Report form (eCRF).…”
Section: Methodsmentioning
confidence: 99%
“…Clinical studies regarding COPD treatment with the Spiolto Respimat ® inhaler have shown significant improvements in lung function, respiratory symptoms, HRQoL, and exercise capacity [ 15 , 16 , 17 , 18 , 19 ]. In a recently published, real-world, observational study of Valipour et al, treatment with tiotropium–olodaterol via a Spiolto Respimat ® inhaler confirmed those results as an improvement in self-reported HRQoL, as assessed by the Clinical COPD Questionnaire (CCQ) [ 20 ].…”
Section: Introductionmentioning
confidence: 86%
“…This non-interventional study was an open-label, self-controlled, single-arm, observational study enrolling male and female patients aged ≥40 years with confirmed diagnosis of COPD receiving tiotropium–olodaterol delivered via Spiolto Respimat ® soft mist inhaler. A detailed description of the study design has been published previously by Valipour et al [ 20 ]. Briefly, GOLD patients from group B, C, or D (GOLD COPD Strategy Document 2018) [ 1 ] were consecutively enrolled upon the decision of their treating physician and in accordance with approved summary of product characteristics (SmPC) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation